1994
DOI: 10.1159/000227348
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Metastatic Colorectal Cancer Patients with 5-Fluorouracil in Combination with Recombinant Subcutaneous Human lnterleukin-2 and Alpha-lnterferon

Abstract: We treated 14 patients with progressive metastatic colorectal cancer, using a combination of subcutaneous recombinant human interleukin-2 (4.8 × 106 IU/m2 three times daily on days 1 and 22, and twice daily on days 2 and 23, followed by 2.4 × 106 IU/m2 twice daily on days 3-5, 8-12, 24-26, and on 5 consecutive days per week, starting day 29), recombinant human interferon-α2a (5.0 × 106 U/m2 thrice weekly), and 5-fluorouracil (750 mg/m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Rather than being immunosuppressive, the use of 5-FU + leucovorin appeared to augment natural killer (NK) and lymphokine-activated killer (LAK) activity. Promising clinical results were recently reported by Yang et al (1993) applying a combination of 5-FU, leucovorin and IL-2, and by Atzpodien et al (1994) using a combination of 5-FU, IL-2 and IFNa-2a in metastatic colorectal cancer. These studies provided the basis for the design of the study reported here with a schedule of IL-2, IFNa-2a and 5-FU in patients with advanced colorectal cancer.…”
mentioning
confidence: 88%
“…Rather than being immunosuppressive, the use of 5-FU + leucovorin appeared to augment natural killer (NK) and lymphokine-activated killer (LAK) activity. Promising clinical results were recently reported by Yang et al (1993) applying a combination of 5-FU, leucovorin and IL-2, and by Atzpodien et al (1994) using a combination of 5-FU, IL-2 and IFNa-2a in metastatic colorectal cancer. These studies provided the basis for the design of the study reported here with a schedule of IL-2, IFNa-2a and 5-FU in patients with advanced colorectal cancer.…”
mentioning
confidence: 88%